Association of interleukin-33 gene polymorphisms with susceptibility to late onset Alzheimer’s disease: a meta-analysis - Zhong X; Liu M; He M; Du K; Wei M (Neuropsychiatric Disease and Treatment, 2017)
Xin Zhong,1,2 Ming-Yan Liu,1,2 Miao He,1,2 Ke Du,1,2 Min-Jie Wei1,2 1Department of Pharmacology, School of Pharmacy, China Medical University, 2Liaoning Key Laboratory of Molecular Targeted Anti-Tumor Drug Development and Evaluation, Shenyang, Liaoning Province, People’s Republic of China Abstract: The association between interleukin-33 (IL-33) gene polymorphisms and late onset Alzheimer’s disease (LOAD) remains controversial in previous studies. Thus, a meta-analysis was conducted to assess the association between the IL-33 polymorphisms (rs11792633 and rs7044343) and LOAD susceptibility. Crude odds ratio (OR) and 95% confidence interval (CI) were used to investigate the relationship strength. Sensitivity analysis was performed, and publication bias was estimated by the Begg’s and Egger’s tests. Overall, six independent studies involving 2,589 patients and 8,414 control samples met our inclusion criteria and were included in this meta-analysis. The results showed that IL-33 rs11792633 polymorphism had statistically significant correlation with a decreased risk of LOAD in heterozygous comparison model (OR =0.64, 95% CI =0.48–0.83), homozygote comparison model (OR =0.83, 95% CI =0.74–0.93), dominant model (OR =0.78, 95% CI =0.67–0.91), recessive model (OR =0.70, 95% CI =0.59–0.84), and allelic model (OR =0.79, 95% CI =0.69–0.91), which were also validated by stratified subgroup analysis. Additionally, there was an apparent association between the IL-33 rs7044343 variant and LOAD risk under four genetic models for overall population (heterozygous comparison model: OR =0.75, 95% CI =0.63–0.89; dominant model: OR =0.83, 95% CI =0.70–0.98; recessive model: OR =0.80, 95% CI =0.68–0.94; allelic model: OR =0.86, 95% CI =0.79–0.94) as well as Caucasian subgroup. In summary, our meta-analysis implicated that IL-33 gene polymorphisms rs11792633 and rs7044343 were significantly associated with the susceptibility of LOAD. Keywords: late onset Alzheimer’s disease, interleukin-33, polymorphism, meta-analysis